A Fossilized Language Pattern for the Singular First Person Subject Pronoun in the Saudi Context: I vs. I am - Mehmet Bulent Rakab (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2018)
The drive that motivated this study was an English as a Foreign Language (EFL) teacher’s observation of a fossilized grammar pattern produced by students over an extended period of time.  The fossilized pattern “I am go” frequently emerges in the EFL context of Saudi Arabia, for which a number of factors could be accountable, including overgeneralization of a grammar pattern, inadequate instruction, lack of negative and corrective feedback, being frequently exposed to peers’ production of the fossilized pattern, and so forth.  155 undergraduate students from a Saudi university responded to a multiple-choice question with three options.  The findings revealed that only one third of the participants identified the correct singular first person subject pronoun in English “I”, which corresponded to (انا) in Arabic.  Based on the results, pedagogical and methodological recommendations are made as to how the possibility of the emergence of the incorrect pattern in question can be reduced or minimized.